Evolution of Coronary Computed Tomography Radiation Dose Reduction at a Tertiary Referral Center - Ghoshhajra, Brian Burns (Am J Med, 2012)
PURPOSE: We aimed to assess the temporal change in radiation doses from coronary computed tomography angiography (CCTA) during a 6-year period. High CCTA radiation doses have been reduced by multiple technologies that, if used appropriately, can decrease exposures significantly. METHODS: A total of 1277 examinations performed from 2005 to 2010 were included. Univariate and multivariable regression analysis of patient- and scan-related variables was performed with estimated radiation dose as the main outcome measure. RESULTS: Median doses decreased by 74.8% (P < .001), from 13.1 millisieverts (mSv) (interquartile range 9.3–14.7) in period 1 to 3.3 mSv (1.8–6.7) in period 4. Factors associated with greatest dose reductions (P < .001) were all most frequently applied in period 4: axial-sequential acquisition (univariate: −8.0 mSv [−9.7 to −7.9]), high-pitch helical acquisition (univariate: −8.8 mSv [ − 9.3 to −7.9]), reduced tube voltage (100 vs 120 kV) (univariate: −6.4 mSv [ − 7.4 to −5.4]), and use of automatic exposure control (univariate: −5.3 mSv [ − 6.2 to −4.4]). CONCLUSIONS: CCTA radiation doses were reduced 74.8% through increasing use of dose-saving measures and evolving scanner technology.